Electrocatalysts: Nickel–Cobalt Diselenide 3D Mesoporous Nanosheet Networks Supported on Ni Foam: An All‐pH Highly Efficient Integrated Electrocatalyst for Hydrogen Evolution (Adv. Mater. 19/2017). Issue 19 (May 2017) - Liu, Bin; Zhao, Yu‐Fei; Peng, Hui‐Qing; Zhang, Zhen‐Yu; Sit, Chun‐Kit; Yuen, Muk‐Fung; Zhang, Tie‐Rui; Lee, Chun‐Sing; Zhang, Wen‐Jun
Abstract : Wen‐Jun Zhang and co‐workers demonstrate an integrated electrocatalyst comprising 3D nickel‐cobalt diselenide mesoporous nanosheet networks supported on Ni foam, as reported in article number1606521 . Due to the collective effects of special morphological design and electronic structure engineering by Co doping, the diselenide electrode with optimal Co concentration exhibits prominent hydrogen evolution reaction activity and excellent stability over a wide pH range.